ANALISIS KADAR Hg DAN Cd PADA KIJING AIR TAWAR (Pilsbryconcha exilis) DI SUNGAI DESA LAMASI PANTAI KABUPATEN LUWU - Miftahul Jannah; Nurmalasari; Ridha Yulyani Wardi (Cokroaminoto Journal of Chemical Science)
This study aims to determine the heavy metal content of mercury (Hg) and cadmium (Cd) in the freshwater mussel (Pilsbryoconcha exilis) in the Lamasi Pantai village, Luwu district. This type of research is descriptive research. The instrument used in this research is ICP-MS. The results of the analysis showed the levels of heavy metal Cadmium (Cd) in fresh water mussel (Pilsbryconcha exilis) at the sample station I 0.04 ppm, station II 0.03 ppm, station III 0.06 ppm. The levels of heavy metal Mercury (Hg) at stations I, II, and III were <0.0005 ppm respectively. These results indicate the content of heavy metals contained does not exceed the SNI quality standard of 1.0 ppm.